Maximized Output Power Design of Switch-Mode Power Amplifier with Thevenin Impedance - Manasummakij, Prateep; Pakasiri, Chatrpol (My University, 2020)
This paper presents a class-E power amplifier circuit designed using Thevenin impedance. The aim of the method is to maximize the output power of the circuit. The measured results showed that the proposed method yielded output power of 24.33 dBm comparing to 24.99 dBm of the simulated one.
Keywords: class-E; maximize power; switch-mode power amplifier; Thevenin impedance